Sugar-Sweetened Beverages and Obesity among Children and Adolescents: A Review of Systematic Literature Reviews - Keller, Amélie (Child Obes, 2015)
Background: The prevalence of overweight and obesity among children and adolescents has increased worldwide and has reached alarming proportions. Currently, sugar-sweetened beverages (SSBs) are the primary source of added sugar in the diet of children and adolescents. Contradictive findings from studies and reviews have fueled an endless debate on the role of SSBs in the development of childhood obesity. Methods: The primary aim of the present review of reviews was to assess how review- and study-level methodological factors explain conflicting results across reviews and meta-analyses by providing an up-to-date synthesis of recent evidence regarding the association between SSB consumption and weight gain, overweight, and obesity in a population of 6-month-old to 19-year-old children and adolescents. The secondary aim was to assess the quality of included reviews using the Assessment of Multiple SysTemAtic Reviews (AMSTAR) measurement tool. Systematic literature reviews and meta-analyses were included. The literature search was performed through the platforms Pubmed/Medline, Cinahl, and Web of Knowledge. Results: Thirteen reviews and meta-analyses were included. Nine reviews concluded that there was a direct association between SSBs and obesity in children and adolescents and four others did not. The quality of the included reviews was low to moderate, and the two reviews with the highest quality scores showed discrepant results. Conclusions: The majority of reviews concluded that there was a direct association between SSB consumption and weight gain, overweight, and obesity in children and adolescents. However, recent evidence from well-conducted meta-analyses shows discrepant results regarding the association between SSB and weight gain, overweight, and obesity among children and adolescents. Improving methodological quality of studies and reviews as well as ensuring responsible conduct of research and scientific integrity is essential for the provision of objective results.